High expression of MARVELD3 as a potential prognostic biomarker for oral squamous cell carcinoma - Huang, Ke; Meng, Yucheng; Lu, Jiyuan; Xu, Lingdan; Wang, Shiqi; Wang, Huihui; Xu, Zhaoqing (Frontiers in Genetics, 2022)
Objectives: Tight junction-associated marvel proteins (TAMP) is a transmembrane protein whose members are associated with tight junctions between cells and epithelial remodeling. MARVEL domain containing 3 (MARVELD3) is one of the members of the TAMP. MARVELD3, as a novel tight junction protein involved in bicellular tight junction assembly, has attracted growing attention in the field of oncology. This study aimed to investigate the prognostic role of MARVELD3 and to determine how it functions in tumorigenesis in oral squamous cell carcinoma (OSCC), thus providing additional data to help the guidance of clinical practice. Materials and Methods: RNA-seq data and relevant clinical information were obtained from TCGA. Bioinformatics means used in this study included differential gene expression analysis, KM survival curve analysis, univariate and multivariate Cox regression analyses, nomogram analysis, ROC curve analysis, methylation level analysis, gene function enrichment analysis, and immune cell infiltration analysis. Results:MARVELD3 was significantly higher expressed in OSCC tissue than in normal tissue, and the overall survival of the high expression group was significantly lower than that of the normal group. Univariate and multivariate Cox regression analyses showed that MARVELD3 could serve as an independent contributing factor to poor OSCC prognosis. The nomograms and ROC curves supported the results above. Its expression was negatively correlated with DNA methylation sites. Analysis of PPI networking and gene functional enrichment showed that MARVELD3 was involved in the functional activities of DNA and RNA and was associated with immune cell infiltration. Conclusion: The high expression of MARVELD3 is associated with poor prognosis in OSCC, and MARVELD3 could be recognized as a novel independent prognostic factor for OSCC.